PENINGKATAN LIFE SKILL MELALUI PELATIHAN MEUBEL BAGI KELOMPOK PEMUDA TOBATI DI KELURAHAN VIM DISTRIK ABEPURA KOTA JAYAPURA - Helen Wayangkau; Alfian Adie Chandra; Alfrendy Lolopayung; Robert Frans Horik (JURNAL PENGABDIAN PAPUA, 2022)
Generally unemployment is a social problem that faced by Jayapura government, especially in Tobati youth. Thus it needs to be overcome by life skills education such as guidance and training to improve their knowledge and skills, especially in furniture (meeting tables). In essence, this service activity is expected to be a solution to the problems faced by the community through job skills training activities in order to increase the ability to support the life skills they face.Keywords: Life Skill: Meubel; Jayapura